Molecular Mechanisms That Link Oxidative Stress, Inflammation, and Fibrosis in the Liver - Erika Ramos-Tovar; Pablo Muriel (MDPI AG, 2020)
Activated hepatic stellate cells (HSCs) and myofibroblasts are the main producers of extracellular matrix (ECM) proteins that form the fibrotic tissue that leads to hepatic fibrosis. Reactive oxygen species (ROS) can directly activate HSCs or induce inflammation or programmed cell death, especially pyroptosis, in hepatocytes, which in turn activates HSCs and fibroblasts to produce ECM proteins. Therefore, antioxidants and the nuclear factor E2-related factor-2 signaling pathway play critical roles in modulating the profibrogenic response. The master proinflammatory factors nuclear factor-κB (NF-κB) and the nucleotide-binding oligomerization domain (NOD)-like receptor protein 3 (NLRP3) inflammasome may coordinate to produce and activate profibrogenic molecules such as interleukins 1β and 18, which effectively activate HSCs, to produce large amounts of fibrotic proteins. Furthermore, the NLRP3 inflammasome activates pro-caspase 1, which is upregulated by NF-κB, to produce caspase 1, which induces pyroptosis via gasdermin and the activation of HSCs. ROS play central roles in the activation of the NF-κB and NLRP3 signaling pathways via IκB (an inhibitor of NF-κB) and thioredoxin-interacting protein, respectively, thereby linking the molecular mechanisms of oxidative stress, inflammation and fibrosis. Elucidating these molecular pathways may pave the way for the development of therapeutic tools to interfere with specific targets.